DEVICE FOR INVESTIGATION OF MAGNETRON AND PULSED-LASER PLASMA - A. P. Burmakov; V. A. Zaikov; F. F. Komarov; O. R. Lyudchik; D. A. Saladukha (Приборы и методы измерений)
Various modifications of complex pulsed laser and magnetron deposition thin-film structures unit are presented. They include joint and separate variants of layer deposition. Unit realizes the plasma parameters control and enhances the possibility of laser-plasma and magnetron methods of coatings deposition.